Tectonic evolution and mineralization exploration of Lujing uranium ore field, South China - Weidong Ren; Huan Li; Annan Guan; Shuang Gao; Qianlin Wang; Pingning Ouyang; Haojie Cao; Yu Sun; Fangchao Yan (Scientific Reports)
Abstract Granite-type uranium deposit is one of the most important uranium deposit types in China, with orebodies strongly controlled by structures. Previous studies of the Lujing ore field mainly focused on metallogenic genesis and Yanshanian structure, which left the tectonic evolution process from Caledonian to Indosinian stage in Lujing ore field unclear. Based on field investigation and classical stress inversion method, the tectonic stress field and evolution series are established, with an aim to clarify the tectonic evolution process of Lujing ore field. The results show that Lujing ore field has underwent NW-trending compression deformation at Caledonian stage, NE-trending compression deformation at indosinian stage, NW-trending compression deformation at early Yanshanian stage and NW-trending tensional deformation at late Yanshanian stage. The ore-controlling structure is mainly NE-trending, while the intersection between NW- and NE-trending structure has giant mineralization potential. Combined with field observation results, we delineated two prospecting area in the intersection between NW- and NE-trending structure in northern part of the Huangfengling and Fengshuxia ore area. This study provides new insights into tectonic evolution in Nanling area, and indicate that the classical stress inversion method is useful for clarifying the tectonic evolution process and uranium ore prospecting.